Sustainable solutions to emerging environmental quality problems in Menemen agricultural plain - Müezzynoòlu A.; Türkman A.; Panahy M.; Elbyr T. (Interdependency between agriculture and urbanization: Conflicts on sustainable use of soil and water, 2001)
Menemen plain that is located by the Aegean Sea at the western part of Turkey covers an area of 23.000 ha. This plain, is a very rich one producing traditional crops. Irrigation water problems have been emerging during the last decades, due to limitations of water resources connected with compatible uses of surface and groundwater reserves as well as due to pollution risks. Presently there are plans to use the treated effluents of the wastewater treatment facility of the city of Izmir (3 million population equivalent) for Menemen Plain irrigation. However, it is suspected that soil is already endangered by several polluting factors. Along with water pollution problems, Menemen plain is under the risk of atmospheric depositions from the large industrial premises located at the north and competing land-uses due to extending urbanisation plans from Izmir. In this study, environmental quality deterioration with respect to soil, groundwater and surface water properties, air quality and the quality of precipitation in the area is discussed.
Seminar: Interdependency between Agriculture and Urbanization: Conflicts on Sustainable Use of Soil and Water, 2000/04/02-06, Tunis (Tunisia)